The policy and practice of reclaimer integration in the City of Johannesburg - Sekhwela, Maite Mmakgomo (My University, 2017)
Reclaimer integration in South Africa has been identified as a priority, but how to integrate reclaimers remains a challenge. Crucially, there is not yet a coherent approach or a clear understanding of what reclaimer integration means in South Africa, let alone whether this same understanding of integration is shared by the reclaimers who are being integrated. By focusing on the integration initiatives of the Environment and Infrastructure Services Department (EISD) and Pikitup, this thesis conducts a comparative study of two reclaimer integration projects in Johannesburg. It investigates the breakdown and mismatch of understandings between social actors who do not share the same view of integration and implications thereof. In doing so, it contributes to discourse on the transformation of Johannesburg’s waste management system. Social constructivism theory by Berger and Luckmann (1966) provides the theoretical grounding for this dissertation by exploring how different milieus and experiences shape people’s understanding of realities. Findings illustrate that there is no clear conceptualisation of integration that underpins waste management policy. Drawing on social constructivism theory, the paper concludes that integration is a socially constructed and contested concept. Essentially, there are inconsistent understandings of integration among different groups of reclaimers as well as officials. For that reason, integration programmes created a new form of exclusion and imposed negative effects on reclaimers. KEYWORDS: Integration, Reclaimers, Waste, Policy, Recycling, cooperatives
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science (Geography). Johannesburg, 11 June 2017.
Keywords: Integrated solid waste management; Recycling (Waste, etc.)--South Africa--Johannesburg; Environmental management--South Africa--Johannesburg; Environmental policy; Management--Environmental aspects